Global approaches to older abuse research in institutional care settings: A systematic review. - Maria Agaliotis; Tracey Morris; Ilan Katz; David Greenfield (PLoS ONE)
Background Over the last two decades, abuse of older adults in institutional settings has been underestimated due to challenges in defining and responding to the issue. This systematic review aims to analyze empirical studies on measuring abuse of older people residing in a long-term care facility, specifically staff-to-resident abuse. Methods Following PRISMA guidelines, we searched 10 databases from January 2005 till June 2024. Inclusion criteria encompassed World Health Organization-defined abuse types (physical, psychological, financial, sexual and neglect, intentional or unintentional), reported by staff, residents, family, or public registries, with methodological critical assessment. Findings In the last 18 years, 22 studies from eight counties examined of staff-to-resident abuse, with significant heterogeneity in definitions, reporting sources, and measurement tools. Quality of studies varied, lacking consistency. Relatives and staff typically report highest abuse rates, while residents report fewer incidents, even with fewer incidents of observed abuse. Registries tend to capture extreme cases, resulting in lower reported prevalence rates, particularly of physical or sexual abuse and neglect. Physical abuse was the most reported, with 81 different descriptors identified and varying recall periods. Staff witnessing abuse ranged from 44% over four weeks to as low as 1.4% over 12 months, posing challenges for data interpretation. Conclusion These variations in study methodologies impacted the ability to synthesise the findings making it difficult to estimate a global prevalence rate of aged care abuse. From the analysis, we develop an Aged Care Abuse Research Checklist (ACARC) as a first step towards achieving a global standardized, evidence-based methodology for this field. Doing so will normalize processes within organizations and the community, allowing early interventions to change practices, reduce the risk of recurrence and improve resident quality of care and workplace cultures. Registration number PROSPERO CRD42018055484.